2016
DOI: 10.1088/1748-0221/11/05/p05023
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of PARIS LaBr3(Ce)-NaI(Tl) phoswich detectors up toEγ∼ 22 MeV

Abstract: In order to understand the performance of the PARIS (Photon Array for the studies with Radioactive Ion and Stable beams) detector, detailed characterization of two individual phoswich (LaBr 3 (Ce)-NaI(Tl)) elements has been carried out. The detector response is investigated over a wide range of E γ = 0.6 to 22.6 MeV using radioactive sources and employing 11 B(p, γ) reaction at E p = 163 keV and E p = 7.2 MeV. The linearity of energy response of the LaBr 3 (Ce) detector is tested upto 22.6 MeV using three diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This read-out was also tested with fast-responding scintillators, e.g. PARIS [42,43] and FATIMA [44,45] for which time resolution of ∼250 ps is obtained using the V1730 digitizers [46].…”
Section: High-energy γ Raysmentioning
confidence: 99%
“…This read-out was also tested with fast-responding scintillators, e.g. PARIS [42,43] and FATIMA [44,45] for which time resolution of ∼250 ps is obtained using the V1730 digitizers [46].…”
Section: High-energy γ Raysmentioning
confidence: 99%
“…Each element is made up of 2 ′′ × 2 ′′ ×2 ′′ LaBr 3 (Ce) crystal optically coupled to a 2 ′′ × 2 ′′ ×6 ′′ NaI(Tl) crystal followed by a single PMT for signal readout. Recently, two PARIS phoswich detector element have been characterized over a wide range of γ-ray energies [8]. In the high energy γ-ray measurement, the evaporated neutrons are the major sources of contamination, which can be rejected by time-of-flight (TOF) technique.…”
Section: Introductionmentioning
confidence: 99%
“…It was proved to be more dependent on the detailed properties of the nuclear force than the IVGDR [15][16][17][18]. Additional experimental information is helpful in this regard such as the observation of a new decay mode in 142 Nd [19], 60 Ni [20], 130 Te [21] and 140 Ce [22] which can provide complementary information on the wave functions of these states. It revealed that the levels associated with PDR have a regular behavior: ∼25% of them decay to excited states.…”
mentioning
confidence: 99%